Peningkatkan Hasil Belajar Peserta Didik melalui Model Pembelajaran Problem Based Learning di Kelas 3 SDN Ngijo 01 Kota Semarang - Sri Wahyuni; Nursiwi Nugraheni; Durratus Sa’diyah (Concept: Journal of Social Humanities and Education, 2023)
He background of this research is the low learning outcomes of students in class III at SDN Ngijo 01 Gunungpati District, Semarang City, because the learning process is still centered on the teacher who still follows the habit in the order that begins with the teacher directly explaining the material, then evaluates students through practice. The expected goal in this study is to improve student learning outcomes in learning with the Problem Based Learning model. This type of research is Classroom Action Research which is focused on action as an effort to improve student learning outcomes by using the Problem Based Learning learning model for class III students at SDN Ngijo 01 Gunungpati District, Semarang City. This research consists of 5 cycles. Each of these cycles includes the stages of planning, implementing, observing and reflecting. The research subjects were class III SDN Ngijo 01 Semarang, totaling 21 students consisting of 10 male students and 11 female students. Data collection methods in this study are tests and observations. The research instruments used in this study were test questions and observation sheets. Data on learning outcomes tests were analyzed in a quantitative descriptive manner and the data in the form of observations were analyzed in a qualitative descriptive manner. The success criteria achieved by students and teachers in this study were seen from changes towards improvement and increasing student learning outcomes. The results of classroom action research carried out by the author in five cycles resulted in an increase in students' learning completeness. This can be seen from the percentage of students who pre-action achieved 38% classical mastery level, namely 8 out of 21 students. From the first cycle of students who completed only 12 or 57% of students' completeness, the second cycle had 62% classical completeness, the third cycle had 71% classical completeness, the fourth cycle had 86% classical completeness, the V cycle had 90% classical completeness. Due to the increase in student learning outcomes from having met the target of 85% so that the cycle ends in cycle V. Students show activeness in the learning process and students also understand more because they have direct learning experiences using the Problem Based Learning learning model. This proves that the Problem Based Learning learning model is able to improve student learning outcomes.